Classifying climate change perceptions of bean breeders in Santander-Colombia. (14th September 2021) - Botero, Hernan; Barnes, Andrew; Perez, Lisset; Rios, David; Ramirez-Villegas, Julian
ABSTRACT: Voluntary uptake of climate-adapted beans is driven by farmers' climate change perceptions. Identifying these perceptions and understanding their determinants help public agencies and seed suppliers design tailored engagement strategies to maximize uptake. We perform the first classification of climate change perceptions among farming communities in Colombia. A latent class analysis (LCA) is applied to a survey designed to capture the climate change perceptions of 566 bean farmers in the Colombian department of Santander. A Multinomial Logistic Model is estimated to determine the drivers behind the climate change perceptions identified. Farmers located at lower elevations and who are further away from their urban centres tend to be more concerned about the future economic consequences of climate change. These farmers also tend to seek climatic information for making productive activities. Accordingly, strategies aimed at maximizing the uptake of new drought-resistant bean varieties should focus on these farmers as they seem to be more receptive to uptake them. Moreover, engagement strategies containing information on management alternatives to appraise uncertainties and mitigate some of the severe effects of extreme weather events will generate increased uptake.